Primary mitral valve regurgitation scheduled for cardiac surgery: no longer need for coronary angiography? A clinical retrospective & HTA analysis. (14th October 2021) - Romeo, M R; Baroni, M; Berti, S; Bianchi, G; Margaryan, R; Solinas, M; Clemente, A; Chiappino, D; Bevilacqua, S; Megaro, M
Abstract: Introduction: In patients (pts) undergoing cardiac surgery for primary mitral regurgitation (PMR), coronary angiography (CA) is always scheduled shortly before surgery to rule out significant coronary artery disease (CAD), despite this population is often young and with relatively low risk for CAD. Computed Tomography Coronary Angiography (CTCA) could be an alternative approach to evaluate coronary arteries, at least ruling out significant CAD in selected pts, due to its high negative predictive value. Purpose: A safer, more appropriate and efficient clinical and diagnostic pathway for patients undergoing cardiac surgery for PMR by stratifying patients prior cardiac surgery according to pretest probability score (PTP) and therefore shifting imaging of epicardial coronary arteries from invasive to noninvasive in specific patients subsets. Methods: A retrospective analysis (Jan 2014–Dec 2020) was carried out through the extraction of 7343 electronic medical records of pts who underwent cardiac valve surgery. In 1556 pts with PMR (1195 with no-CAD and 361 with CAD) a PTP was retrospectively calculated according to Genders, 2012, to stratify their risk of CAD. A Decision oriented Health Technology Assessment (DoHTA) and a cost analysis were also performed to support the analysis results. A survey was distributed to a team of experts with a multidisciplinary background to analyze the most significant evaluation areas (Economic Aspects, Clinical Effectiveness, Safety, Innovation) and the sub-criteria related to them. Following the Core Model Eunethta as a guideline, a Rapid Report HTA has been drawn up to identify the best solution. Results: Patients characteristics are listed in Picture 1. Pts with normal coronary arteries showed a PTP low-to intermediate while pts with high PTP had CAD and therefore had a real pretest need for a CA (average 11 percent ± 9 in noCAD group vs 20 percent ± 14 in the CAD group). In two thirds of PMR population coronary angiography could have been avoided according to a PTP score <15 percent. The cost analysis results were significantly lower in CTCA (1, 315.00 EUR vs 180.00 EUR, CA vs CTCA respectively), The Decision Oriented HTA conducted by a multidisciplinary team showed a relevant preference for the new pathway (Picture 2) with a score of 70.23 percent of preference among the Team. Conclusions: This new pathway, already proposed for selected pts in ESC guidelines on valve diseases (class IIA, LOE C) could be always adopted in PMR pts with low-to intermediate PTP score undergoing cardiac surgery. It could improve workflow efficiency and reduce LOS, and last but not least, avoid an invasive test, reduce radiation exposure and AKI risk in in a relatively young population The DoHTA provided a more effective and efficient support to the decision-making process. Funding Acknowledgement: Type of funding sources: None.